2018
DOI: 10.1016/j.kjms.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel β‐titanium alloy orthodontic wire

Abstract: This literature review investigated a recently developed orthodontic wire composed of a β-titanium alloy known as "Gum Metal" and compared its properties with those of conventional wires. The attractive properties of Gum Metal include an ultra-low Young's modulus, non-linear elastic behavior, ultra-high strength, high yield strain, high ductility, and superplastic deformability without work hardening at room temperature. The unique multifunctional characteristics of this new orthodontic wire make it almost ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…These results are in accordance with Murakami et al [31], which reported a continuous light force delivery for GUMMETAL® compared to TMA and Resolve, both βTi-derived alloys. This plastic behavior without crystal motion dislocation occurs due to oxygen addition and proper cold working [11,12,32]. In contrast, GUMMETAL® delivered lower unloading forces than NiTi and SS when combined with CL brackets; these might be attributed to a wire-bracket interaction, mainly due to the high friction achieved by the ligatures [33].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These results are in accordance with Murakami et al [31], which reported a continuous light force delivery for GUMMETAL® compared to TMA and Resolve, both βTi-derived alloys. This plastic behavior without crystal motion dislocation occurs due to oxygen addition and proper cold working [11,12,32]. In contrast, GUMMETAL® delivered lower unloading forces than NiTi and SS when combined with CL brackets; these might be attributed to a wire-bracket interaction, mainly due to the high friction achieved by the ligatures [33].…”
Section: Discussionmentioning
confidence: 98%
“…Changing wires during orthodontic treatment increases costs and also overall treatment time; additionally, the order of which archwires alloys to employ relies solely on professional experience. The use of GUMMETAL®, a specific type of βTi, has been proposed as a new alloy for orthodontic purposes due its high elasticity, moldability, and low rigidity [11,26]; this wire seems to have the most remarkable mechanical properties described for an orthodontic wire making it suitable for use during all treatment phases [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the introduction of orthodontic appliances that combine the esthetics with optimal performance. [123] In fixed orthodontic therapy, the introduction of esthetic orthodontic brackets partially solved the issue, but most of the orthodontic wire alloys are stainless steel, cobalt-chromium, beta-titanium, and nickel-titanium (NiTi). [4]…”
Section: Introductionmentioning
confidence: 99%
“…Also, such alloys are widely used in medicine as bone-replacement prosthesis and dental implants and instruments due to the biocompatibility of titanium. [1][2][3][4] b titanium alloys show favorable strength to density ratio, combined with good ductility and attractive processing features such as deep hardenability and forging performance. [5] Nowadays, the most often applied b titanium alloys are Ti-10V-2Fe-3Al (Ti-10-2-3), developed in 1970 by Timet Company, and Ti-5Al-5Mo-5V-3Cr (Ti-5553).…”
Section: Introductionmentioning
confidence: 99%